2017
DOI: 10.2174/1570159x14666161101092822
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Resistance in Chronic Pain Management

Abstract: Chronic pain management represents a serious healthcare problem worldwide. Chronic pain affects approximately 20% of the adult European population and is more frequent in women and older people. Unfortunately, its management in the community remains generally unsatisfactory and rarely under the control of currently available analgesics. Opioids have been used as analgesics for a long history and are among the most used drugs; however, while there is no debate over their short term use for pain management, limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 199 publications
0
54
0
3
Order By: Relevance
“…Inadequate pain management led to drug-seeking behaviors that resemble those seen with opioid addiction. This phenomenon is referred to as pseudoaddiction [9,10]. In clinical settings, pseudoaddiction can be distinguished from opioid dependence in that the behaviors disappear after appropriate pain treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate pain management led to drug-seeking behaviors that resemble those seen with opioid addiction. This phenomenon is referred to as pseudoaddiction [9,10]. In clinical settings, pseudoaddiction can be distinguished from opioid dependence in that the behaviors disappear after appropriate pain treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, pseudoaddiction can be distinguished from opioid dependence in that the behaviors disappear after appropriate pain treatment. On the other hand, opioid tolerance develops with repeated opioid exposure, resulting in a decrease in the analgesic effect [10,11]. The development of opioid tolerance has been reported to lead to an increase in opioid consumption and the risk of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of pain in transplant patients may influence physicians to select opioids as a first‐line therapy. The analgesic effect of opioid therapy has been extensively documented . Nevertheless, studies have shown that the perceived analgesic benefits of opioids are often overstated, with one study suggesting that 71% of opioid users reported less than a 30% decrease in general chronic pain …”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of opioid therapy has been extensively documented. 19,20 Nevertheless, studies have shown that the perceived analgesic benefits of opioids are often overstated, with one study suggesting that 71% of opioid users reported less than a 30% decrease in general chronic pain. 21 Adverse effects of chronic opioid use are increasingly described in the literature, yet no studies have reported adverse outcomes associated with these medications in either adult or pediatric LTx recipients, notwithstanding widespread opioid use in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are fundamental to provide relief from cancer pain; however, evidence is lacking for their effectiveness when used for the treatment of chronic non-cancer pain, and these drugs are associated with a number of serious side effects (see Morrone et al, 2017). During the opioid epidemic, from 1999 to 2014, the rate of opioid prescription increased fourfold (Prevention CfDCa, MMWR 2011) and it has been calculated that from 2007 to 2012 one in five patients with non-cancer pain or with a pain-related diagnosis received an opioid prescription for the management of acute and chronic pain (Daubresse et al, 2013).…”
Section: Dear Editorsmentioning
confidence: 99%